The efficacy of divalent iron preparations with and without zinc in the treatment of iron deficiency anemia - Canan Ozdemir, Zeynep; Duzenli Kar, Yeter; Ersozlu, Yasemin; Burcu Caglar, Hatice; Bor, Ozcan (Annals of Medical Research, 2021)
Aim: Iron deficiency anemia (IDA) is the most frequently detected cause of anemia in Turkey and worldwide. In this study, we investigated the efficacy of the iron preparations of ferrous sulfate (group FeS, Fe2+) and ferrous fumarate combined with Zn (group Fe2+-Zn) in the treatment of IDA. Materials and Methods: Seventy children receiving FeS and 24 children receiving Fe2+-Zn due to IDA between June 2018 and January 2019 were included in the study. The Hb, MCV, MCH, RBC, transferrin saturation, ferritin levels before treatment and in the 1st and 3rd months after treatment, period of drug use, and the frequency of gastrointestinal adverse effects in the two groups were investigated. Results: There was no difference between the two groups regarding age and sex. The mean drug dose in FeS group was 4.01±0.98 mg/kg/day and 4.12±0.06 mg/kg/day in the Fe2+-Zn group (p>0.05). The Hb, MCV, MCH, RBC, transferrin saturation, and ferritin levels in both groups in the 1st and 3rd months after treatment were found significantly higher compared with the levels before treatment. No difference was detected between the two groups for the same parameters before treatment, and in the 1st and 3rd months after treatment (p>0.05, for all). The period of drug use in Fe2+-Zn group (median:4.5 months) was longer than in the FeS group (median:4 months) (p0.05). Conclusion: We found that FeS and Fe2+-Zn preparations had similar effects on hematologic parameters and iron status in IDA; however, the treatment period in patients who received Fe2+-Zn was longer.
Keywords: Iron deficiency anemia; divalent iron; zinco